Simulating the ENSO impact on the distribution and fate of floating litter particles in the Northern South China Sea - Pang, Ke; Feng, Yang; Zheng, Youchang; Fang, Chao; Xu, Xiangrong (Frontiers in Marine Science, 2025)
The Pearl River delivers a large amount of plastic waste to the Pearl River Estuary (PRE) and adjacent Northern South China Sea (NSCS) region each year. However, the transport of floating litter after release is difficult to predict due to the complex hydrodynamic conditions caused by the climate variability. A regional ocean circulation model coupled with a Lagrangian particle tracking model is utilized in this study to simulate the distribution and fate of floating litter particles in the Pearl River Estuary (PRE) and Northern South China Sea (NSCS) under the influence of El Niño - Southern Oscillation (ENSO) event. Simulations are conducted during all four seasons (spring, summer, fall, and winter) in typical El Niño, La Niña, and ENSO-neutral year. The model reveals that most floating litter remains within Lingding Bay before being transported westward by the counterclockwise circulation over the NSCS and arriving at the Qiongzhou Strait. After crossing the Strait, the debris is carried by the counterclockwise circulation of the Beibu Gulf, and eventually arriving at the coasts of Vietnam and Laos. The ENSO warm (El Niño) and cold (La Niña) phases disrupt circulation patterns and modulate the amount of Pearl River runoff, thereby altering the transport pathways and grounding probabilities of floating litter. During La Niña years, floating litter particles spread over a wider area, travel longer distances, and have lower beaching probabilities. Conversely, during El Niño year, floating litter particles tend to remain within Lingding Bay for longer durations, with some debris entrained towards the Hong Kong region. This study underscores the impact of climate mode of variability in influencing the litter sources, fate and transport and accumulation at estuarine-coastal oceans, which will provide critical scientific insights for plastic pollution management in the PRE - NSCS region, which is a newly identified hotspot for floating litter and microplastic pollution in global oceans.